Implementasi Metode Profile Matching dalam Pengambilan Keputusan Rekrutmen Wartawan Baru pada PT. Media XYZ - Syahrani Nur Hakim; Desi Pibriana (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
PT. Media XYZ is experiencing a high turnover rate of journalists due to a less objective selection process. The assessment carried out by HRD is currently still subjective and inaccurate. This has an impact on the company's performance and the quality of the news produced. Therefore, a decision-making model is needed that can be used as a guideline by HRD in order to overcome the mismatch between journalist qualifications and job requirements by implementing the Profile Matching method in the journalist selection process. This method will help companies select prospective employees who best match the required competency profile. By matching the competency profile of prospective employees with the competency profile of the position, it is expected to improve the quality of selection decisions, reduce the level of errors in recruitment, and improve company performance.